ANALISIS PREDIKSI KUALITAS TIDUR BERDASARKAN GAYA HIDUP MENGGUNAKAN METODE C4.5 - Andi Sanjaya; Naufal Daffa Erlangga; Mohammad Badrul; Fajar Mustofa; Muhammad Rakha Eka Fernada; Muhammad Pashya Mahesa Farhat; Christian Nicolaus Leonardo Tambunan (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2026)
Insomnia is a common sleep disorder characterized by difficulty sleeping, which results in poor sleep quality. This condition can lead to various negative impacts such as fatigue, decreased productivity, and mental health problems. The natural sleep cycle can be disrupted by modern lifestyle habits, for example, high levels of stress at work, a lack of physical activity, and inadequate sleep duration. To analyze and classify these lifestyle factors, a predictive model will be built using the